Myroides spp. cellulitis and bacteremia: A case report. (2019) - Meyer, Amy; Dang, Harry; Roland, William
Abstract: Myroides spp., formerly Flavobacterium spp ., are gram-negative, non-motile, traditionally opportunistic pathogens that are infrequent clinical isolates. Myroides spp. have been pathogenically implicated in only 52 reported cases since the discovery of the Flavobacterium genus in the 1920s. We present a case of Myroides spp. lower extremity cellulitis and bacteremia. To our knowledge, this is the 16th case of cutaneous infection caused by Myroides spp. Etiology of this patient's infection was felt to be related to exposure of his pre-existing lower extremity wounds to soil and water versus a dog lick in the context of relative immunosuppression from type 2 diabetes and chronic inhaled steroid use. Given the characteristic multi-drug resistance of Myroides spp., resistance to usual empiric antimicrobials given for cellulitis, and potential for fatal infection in cases of pan-resistance, it is important that clinicians remain alert to the possibility of this rare pathogen.